SWIMMING AND CRAWLING BEHAVIOUR OF SCHISTOSOMA SPINDALE (MONTGOMERY, 1906) - KATHI, DANIEL; AGARAPU, JOSEPH (The Bioscan, 2010)
Rotary Video microscopic observations were made to study the swimming and crawling behaviour of cercariae of Schistosoma spindale. Continuous, forward, backward, spiral, sinusoidal and intermittent movements have been studied and their significance in the water medium was described. Specifications in swimming activity of cercaria are briefly discussed. Forward and backward swimming modes were the common observations and the role of furcal ramii along with wave form of body and tail of cercaria has been described. The crawling behaviour of cercariae was observed on substratum after exhaustive swimming activity for a longer period. During the crawling behaviour the correlation between the suckers, and the contraction and expansion of the body muscles of cercariae are described